The aftermath : based on original records, 1818-1826 - Choksey, R. D. (Rustom Dinshaw), 1914- (SAMP early 20th-century Indian books project ;, 1950)
Account of the administrative and judicial changes introduced by the early British administrators in Maharashtra.